2-Cyclohexyl-4-methyltetrahydropyran-4-ol - Tiekink, E.R.T.; Macedo, A.; Wendler, E.P.; Dos Santos, A.A.; Zukerman-Schpector, J. (International Union of Crystallography, 2010)
In the title compound, C(12)H(22)O(2), the 4-methyltetrahydropyran-4-ol ring adopts a conformation close to that of a chair and with the two O atoms syn; the cyclohexyl group occupies an equatorial position and adopts a chair conformation. In the crystal packing, supramolecular chains along the b axis are sustained by O-H center dot center dot center dot O hydrogen bonds. These are connected into undulating layers in the ab plane by C-H center dot center dot center dot O interactions.